Development of a high-quality oat production chain for human consumption - Saastamoinen, Marketta; Lehtomäki, Ilkka; Haapiainen, Jenni; Vesanen, Kaija; Hietaniemi, Veli (MTT, 2004)
The European Agricultural Guidance and Guarantee Fund financed a 3-year project 'The Development of Competence for Oat Production in Satakunta', in which an integrated cultivation and processing chain for high-quality oats and oat products was developed. The objective was to achieve production of high- -glucan oats and oat products with minimum levels of toxic compounds. About 150 farmers sent oat samples and cultivation registers including information on soil nutrients, fertilization, sowing, rainfall and harvest data. The -glucan content and quality of the samples were measured and the toxic compounds cadmium, mycotoxins and pesticides were analysed. In addition, the Falling number of the oat samples, molecular mass of the -glucan and viscosity of the oat cultivars were determined. The? -glucan level was dependent mostly on cultivar and climate. The Falling number and vis-cosity behaviour indicated the quality of the -glucan. In Finnish oat cultivars the differences in molecular mass of the -glucan were small. The Falling number levels of the good-quality Finnish oat cultivars varied only slightly. The Falling number is considered as one of the most important oat purchasing criteria. The cadmium contents of approved oat cultivars were well below the limit of 100 g/kg. The mycotoxin levels were very low and no mycotoxins were found to concentrate in any of product fractions during processing. Only one pesticide, clopyralid, was found among the oat samples. The use of clopyralid-containing pesticides is now prohibited during cultivation. The approved oat cultivars were chosen according to their high -glucan and low cadmium levels. For example, the oat cultivars Salo and Virma are not acceptable for NATUREAL Oat Bran production due to their high levels of cadmium. Cultivation instructions were developed and farmers were educated in the techniques of high-quality oat production using the analysis results of their own samples.
Keywords: Ka; production chain; oat; Avena sativa L; B-glucan content; cadmium content; pesticides